2008
DOI: 10.1002/da.20467
|View full text |Cite
|
Sign up to set email alerts
|

Which symptoms predict recurrence of depression in women treated with maintenance interpersonal psychotherapy?

Abstract: Background-Even low levels of residual symptoms are known to increase the risk of relapse and early recurrence of major depression. It is not known if ongoing psychotherapy lessens this risk. We therefore examined the impact of persistent symptoms, including mood, insomnia, and anxiety symptoms, on time to recurrence in women receiving maintenance interpersonal psychotherapy (IPT-M) for recurrent depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 58 publications
2
60
0
2
Order By: Relevance
“…38) Insomnia may also indirectly elevate cardiovascular risk via comorbid psychological distress. Insomnia is an independent risk factor for major depressive episodes, [39][40][41] increases risk for relapse of depression, 41) perpetuates depression, 42) and is the most common sleep disturbance associated with major depressive episodes. 15) More than 3 of every 4 patients reporting symptoms of insomnia in the present study endorsed moderate or severe depressive symptoms, and nearly 2 of every 3 reported anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…38) Insomnia may also indirectly elevate cardiovascular risk via comorbid psychological distress. Insomnia is an independent risk factor for major depressive episodes, [39][40][41] increases risk for relapse of depression, 41) perpetuates depression, 42) and is the most common sleep disturbance associated with major depressive episodes. 15) More than 3 of every 4 patients reporting symptoms of insomnia in the present study endorsed moderate or severe depressive symptoms, and nearly 2 of every 3 reported anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis, compared to people with no sleep difficulties, non-depressed people with insomnia were predicted to have a twofold increased risk of developing depression (Baglioni et al, 2011). Depressed patients suffering from insomnia also have a poorer response to treatment and are at increased risk of relapse (Dombrovski et al, 2008).…”
Section: The Relationship Between Sleep and Depressionmentioning
confidence: 99%
“…Persistent disturbed sleep after successful treatment of depression increases the risk of reoccurrence of a depressive episode [24][25][26]. This relationship has been observed following a variety of treatments and in different samples, including older adults [26], non-older adult women [24], and pregnant women [25].…”
Section: Residual Insomnia Predicts Relapse and Recurrencementioning
confidence: 99%